Pesantren Dan Tantangan Modernisasi Dalam Buku Menggerakkan Tradisi Karya Kh. Abdurrahman Wahid - Isnaning Tyastuti (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2018)
Pesantren is a traditional Islamic education institution, is an original institution that is owned by Indonesia and has its own unique characteristics. It is said to be unique because the pesantren has a traditional education mechanism tecnicals and has a tradition that not all educational institutions have. The rapid flow of globalization has threatened the existence of pesantren, so that the concept of modernization emerged in the pesantren environment to answer the challenges of the all-modern globalization in all aspects. This study aims to show a comprehensive picture, idea, and concept in the attitude of pesantren facing the era of modernization so that the existence of boarding schools remains by combining the concept of traditional education with modern education without leaving the characteristics of pesantren education that has become the identity of a pesantren. This research is a qualitative study of literature (library research) using documentation methods and using the type of taxonomy analysis that is analysis that focuses attention on a particular domain that is very useful to describe the phenomenon or problem that is the target of the study. This research resulted in modernization described by KH. Abdurrahman Wahid is a response to the condition of Islamic Education, especially pesantren in the present. Modernization is conceptualized in order to provide input or solutions to Islamic education, especially pesantren, so that its existence is maintained in the current era of globalization. The existence of pesantren with the challenges of modernization according to KH. Abdurrahman Wahid must be defended by constantly developing pesantren from various aspects of economics, social culture, revitalization in scientific education, revitalization in humansizm dinamics education, and especially education in pesantren.